Estimación del stock de carbono en especies arbóreas como aporte a la sostenibilidad ambiental, La Fortuna, Manga del Cura, Manabí. - Muñoz Intriago, Otto Andrés (2018)
The vegetal cover present in the community forest of La Manga del Cura, Manabí province, is a territory rich in plant cover, which is home to the native Piedmont forest of the Equatorial Pacific Coastal Range (BePc02) categorized by the Ministry of Environment of the Ecuador (MAE, 2014), with an area of approximately 11.4 ha, of forest. The objective of this research is to estimate the carbon stock of tree species as a contribution to environmental sustainability, the methodology used to know the carbon stock in tree species was the one proposed by the international guidelines for the measurement of stored carbon, such as VCS (2008), MacDicken (1997), and the IPCC guide (2003), without altering the ecological balance of the area. From the field work and the application of the aforementioned methodology it was possible to identify 31 species with the DAP <1.30m., represented in a total of 663 individuals, with five species being the most abundant, the Clarisia biflora (6%) with (43 individuals) , Castilla elastic (6%) with (39 individuals), Beloperone guttata (5%) with (32 individuals), Maclura tinctoria (5%) with (30 individuals) and Hibiscus elatus (4%) with (29 individuals), these species represent 26% of total individuals. We used the allometric equation proposed by the IPCC (2003), where it showed a total result of 481.86 tons. Carbon stock ha / year, showing us that the research carried out in the La Fortuna community is of high environmental importance due to the carbon stock it stores.